Dhwani: Secure Peer-to-Peer Acoustic NFC - and Chintalapudi, Krishna; Padmanabhan, Venkat; Venkatesan, Ramarathnam (SIGCOMM, 2013)
Near Field Communication (NFC) enables physically proximate devices to communicate over very over short ranges in a peer-to-peer manner, without incurring the overhead of any complex network configuration effort. However, the adoption of NFC-enabled applications has been stymied by the low levels of penetration of NFC hardware. In this paper, we address the challenge of enabling NFClike capability on the existing base of mobile phones. To this end, we develop Dhwani, a novel, acoustics-based NFC system that uses the microphone and speakers on mobile phones, thus eliminating the need for any specialized NFC hardware. A key feature of Dhwani is the Jam-Secure technique, which uses self-jamming coupled with self-interference cancellation at the receiver, to provide an information-theoretically secure communication channel between the devices. Our experiments show that Dhwani can achieve data rates of up to 2.4 Kbps, which is sufficient for most existing NFC applications.